2014
DOI: 10.1111/1440-1681.12286
|View full text |Cite
|
Sign up to set email alerts
|

Tracking anti‐fibrotic pathways of nilotinib and imatinib in experimentally induced liver fibrosis: An insight

Abstract: The tyrosine kinase inhibitors imatinib and nilotinib have been suggested to have promising antifibrotic activity in experimental models of liver fibrosis. The aim of the present study was to investigate new pathways underlying this beneficial effect. Hepatic injury was induced in male Wistar rats by intraperitoneal injection of CCl4 for 12 weeks. During the last 8 weeks of treatment, rats were also injected daily intraperitoneally with 20 mg/kg imatinib or 20, 10 or 5 mg/kg nilotinib. At the end of treatment,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 53 publications
(90 reference statements)
3
21
0
Order By: Relevance
“…The activation of HSCs results in the production of α‐SMA, expressing myofibroblasts, followed by the formation of type I collagen and ultimately fibrotic bundles . Therefore, dose‐dependent decrease in the expression of α‐SMA, CTGF, and PDGF was in line with the in vivo antifibrotic effects of these compounds, and also consistent with previous studies . Regarding the effect of the RhoA/ROCK pathway on the expression of CTGF, and PDGF, inhibition of this pathway can prevent the activation of HSCS, the expression of α‐SMA and the production of ECM.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The activation of HSCs results in the production of α‐SMA, expressing myofibroblasts, followed by the formation of type I collagen and ultimately fibrotic bundles . Therefore, dose‐dependent decrease in the expression of α‐SMA, CTGF, and PDGF was in line with the in vivo antifibrotic effects of these compounds, and also consistent with previous studies . Regarding the effect of the RhoA/ROCK pathway on the expression of CTGF, and PDGF, inhibition of this pathway can prevent the activation of HSCS, the expression of α‐SMA and the production of ECM.…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, the inhibition of some RTKs pathway components such as VEGFR and PDGFR, and nRTKs such as c‐Abl, and c‐Src, along with rho‐kinase, led to the development of different treatments …”
Section: Introductionmentioning
confidence: 99%
“…It was found that sorafenib could inhibit proliferation of HSCs by downregulating expression of cyclins and cyclin dependent kinases (CDKs) and prevent ERK, Akt and 70-kDa ribosomal S6 kinase (p70S6K) from phosphorylation [11, 12], [13]. In addition, several other TKIs, such as imatinib [14], vatalanib [15–17], nilotinib [1822], erlotinib [23, 24] and brivanib [25, 26], were also found to prevent HSC activation, resulting in less collagen deposition.…”
Section: Anti-fibrotic Activity Of Tyrosine Kinase Inhibitors: a Potementioning
confidence: 99%
“…Several studies showed that Nilotinib can control hepatic fibrosis by regulating levels of proinflammatory cytokines, primarily interleukin-(IL-) 1 and IL-6 [6][7][8][9]. In an earlier study, we compared Nilotinib, Imatinib, and silymarin in their effect as antifibrotic agents [4]; we found that Nilotinib is better than silymarin and less toxic than Imatinib, and also, we found that Nilotinib induces apoptosis and autophagic cell death of activated hepatic stellate cells via inhibition of histone deacetylases [7].…”
Section: Introductionmentioning
confidence: 99%